Characterization of biogenic hydroxyapatite derived from animal bones for biomedical applications. Issue 9 (15th June 2018) - Ramesh, S.; Loo, Z.Z.; Tan, C.Y.; Chew, W.J. Kelvin; Ching, Y.C.; Tarlochan, F.; Chandran, Hari; Krishnasamy, S.; Bang, L.T.; Sarhan, Ahmed A.D.
Abstract: In this work, the viability of producing biogenic hydroxyapatite from bio-waste animal bones, namely bovine (cow), caprine (goat) and galline (chicken), through a heat treatment process has been investigated. The animal bones were locally sourced, cleaned to remove collagen and subsequently heat treated in air atmosphere at different temperatures ranging from 600 °C to 1000 °C. From the range of sintering temperatures investigated, it was found that hydroxyapatite derived from bovine bone showed good thermal stability while those produced from caprine and galline bones exhibited phase instability with traces of tri-calcium phosphate (TCP) being detected after heat treatment beyond 700 °C. The porous nature of the bone samples can be observed from the microstructures obtained and supported by low relative density. Heating the bovine and caprine bones at selected temperatures yielded porous HA body, having hardness values that are comparable with human cortical bone. However, the sintered galline bone sample showed higher porosity levels and low hardness when compared to the other two bone types.